Wnt-induced dephosphorylation of Axin releases β-catenin from the Axin complex - Willert, Karl (Cold Spring Harbor Laboratory Press, 1999)
The stabilization of β-catenin is a key regulatory step during cell fate changes and transformations to tumor cells. Several interacting proteins, including Axin, APC, and the protein kinase GSK-3β are implicated in regulating β-catenin phosphorylation and its subsequent degradation. Wnt signaling stabilizes β-catenin, but it was not clear whether and how Wnt signaling regulates the β-catenin complex. Here we show that Axin is dephosphorylated in response to Wnt signaling. The dephosphorylated Axin binds β-catenin less efficiently than the phosphorylated form. Thus, Wnt signaling lowers Axin’s affinity for β-catenin, thereby disengaging β-catenin from the degradation machinery.